The philosophy of higher education of the 21st century. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
An educational system can never be organized along Utopian lines. It is constrained by the possibilities that exist within the socio-politico and economic infrastructure from where it springs from and whose benevolence it feeds and nurtures on. An educational system is viable as long as it retains its legitimacy and contributes to the overall growth and harmony of the socio-politico and economic environment.